2005
DOI: 10.1097/00008390-200502000-00005
|View full text |Cite
|
Sign up to set email alerts
|

ErbB receptors mediate both migratory and proliferative activities in human melanocytes and melanoma cells

Abstract: Epidermal growth factor receptor (EGFR) activation by transforming growth factor alpha (TGFalpha) has been implicated in autocrine growth in melanoma, but does not alter melanocyte proliferation. This raises the possibility that different signalling pathways are activated via EGFR or ErbB receptors. Here, we demonstrate that ErbB2, ErbB3 and ErbB4 are expressed in cultured human melanocytes. Western analyses with receptor-specific antisera revealed protein bands with Mr values of 185 and 160 kDa, corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 0 publications
2
46
1
Order By: Relevance
“…Normal human melanocytes express EGFR, ERBB2, ERBB3 and ERBB4, and stimulation with ligand promotes migration in vitro (Gordon-Thomson et al, 2001;Stove et al, 2003;Gordon-Thomson et al, 2005;Mirmohammadsadegh et al, 2005). ErbB receptors also are expressed in melanoma cells, and are associated with melanoma progression in a teleost model (Wellbrock et al, 2002;Gomez et al, 2004) and with human melanoma proliferation in vitro (Stove et al, 2003;Gordon-Thomson et al, 2005;Funes et al, 2006). Our finding that the picasso mutant phenotype results from lesions in erbb3b provides the first evidence that ErbB signals are required to promote normal pigment cell and pigment pattern development in vivo [although Fitch et al (Fitch et al, 2003) describe melanocytosis resulting from EGFR overexpression in skin].…”
Section: Discussionmentioning
confidence: 99%
“…Normal human melanocytes express EGFR, ERBB2, ERBB3 and ERBB4, and stimulation with ligand promotes migration in vitro (Gordon-Thomson et al, 2001;Stove et al, 2003;Gordon-Thomson et al, 2005;Mirmohammadsadegh et al, 2005). ErbB receptors also are expressed in melanoma cells, and are associated with melanoma progression in a teleost model (Wellbrock et al, 2002;Gomez et al, 2004) and with human melanoma proliferation in vitro (Stove et al, 2003;Gordon-Thomson et al, 2005;Funes et al, 2006). Our finding that the picasso mutant phenotype results from lesions in erbb3b provides the first evidence that ErbB signals are required to promote normal pigment cell and pigment pattern development in vivo [although Fitch et al (Fitch et al, 2003) describe melanocytosis resulting from EGFR overexpression in skin].…”
Section: Discussionmentioning
confidence: 99%
“…312,313 Although another investigation reported that ERBB3 was found in only a minority of melanomas, and only in those that were not metastatic, 314 and several melanoma cell lines did not express ERBB3, 315 ERBB3 showed a fourfold increase in expression in melanoma micrometastases and 14-fold increase in macrometastases, compared with normal lymph nodes. 316 NRG-stimulated migration but not proliferation of melanocytes, and had the opposite effect in two melanoma cell lines, 317 suggesting qualitative changes in ERBB pathway signaling during melanoma development. Muc4, a transmembrane mucin that promotes growth and metastasis of melanoma cells, caused increased membrane localization and stability of ERBB2 and ERBB3.…”
Section: Melanomasmentioning
confidence: 97%
“…Because NRG-1-ErbB signaling has been recently reported to affect melanocyte development and melanoma migration (Gordon-Thomson et al, 2005;Buac et al, 2009), the result was of immediate interest. To validate the expression of NRG-1 by fibroblasts at the protein level, we used immunohistochemistry to examine the expression of NRG-1 in normal human skin samples from types I and VI skin ( Fig.…”
Section: Expression Of Nrg-1 In Normal Human Skin and In Cultured Normentioning
confidence: 99%